1995
DOI: 10.1063/1.113111
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of (100)-oriented metallic LaNiO3 thin films on Si substrates by radio frequency magnetron sputtering for the growth of textured Pb(Zr0.53Ti0.47)O3

Abstract: Highly (100)-oriented LaNiO3(LNO) thin films were grown on Si, SiO2/Si, Pt/SiSiO2/Si, as well as glass substrates by rf magnetron sputtering deposition at substrate temperatures ranging from 150 to 500 °C. As-deposited LNO films are metallic; those prepared at substrate temperature ∼150–250 °C have a resistivity of 0.4–0.5 mΩ cm and can be used as the bottom electrode for the fabrication of integrated ferroelectric capacitors on Si. A subsequent deposition of sol-gel derived Pb(Zr0.53Ti0.47)O3 (PZT) thin film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(58 citation statements)
references
References 0 publications
6
50
2
Order By: Relevance
“…In our case, the remnant polarization obtainedishigher than the value of 18.2 µC/cm 2 , as reported on LNO/Si substrate [14]. Othergroupshave also reported that the remnant polarizations were about 19.2 µC/cm 2 and 13.2 µC/cm 2 when the PZT thin films deposited on LNO/poly-Si/titanium nitride (TiN)/SiO 2 /Si wafer and LNO/SiO 2 /Si substrate, respectively [15,16]. Thus, it should be convinced thatthe PZT thin film deposited on LNO/Al foil at the annealing temperature of 600 o C possesses high remnant polarization enough for application of ferroelectric devices.…”
Section: Resultssupporting
confidence: 47%
“…In our case, the remnant polarization obtainedishigher than the value of 18.2 µC/cm 2 , as reported on LNO/Si substrate [14]. Othergroupshave also reported that the remnant polarizations were about 19.2 µC/cm 2 and 13.2 µC/cm 2 when the PZT thin films deposited on LNO/poly-Si/titanium nitride (TiN)/SiO 2 /Si wafer and LNO/SiO 2 /Si substrate, respectively [15,16]. Thus, it should be convinced thatthe PZT thin film deposited on LNO/Al foil at the annealing temperature of 600 o C possesses high remnant polarization enough for application of ferroelectric devices.…”
Section: Resultssupporting
confidence: 47%
“…Stacking buffer layers with perovskite-type lattice surfaces is a prospective approach to achieve the crystal orientation of PZT films on versatile substrates. Some researchers have reported successful results (e.g., using CeO 2 /YSZ or SrTiO 3 buffer layers, 4,7,12 or one-axis-oriented (100)LaNiO 3 template 13,14 ) in which the preferential c-/a-domain formation was realized together with the variation of their ferroelectric/piezoelectric properties. Single-crystal nanosheets of calcium niobate (Ca 2 Nb 3 O 10 ) that possess a pseudo-perovskite-type crystal structure 15,16 are currently being utilized for the buffer layers to control the crystal orientation of perovskite-or layer-perovskite-type dielectric films (SrTiO 3 21 etc.)…”
Section: Introductionmentioning
confidence: 99%
“…A method to control a certain orientation degree Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/ceramint of a film just by tuning the thickness of a seed layer has not been proposed. In this study, different orientations were obtained in LaNiO 3 (LNO) films with different thickness on SiO 2 /Si substrates, which is different from previous reports [16,17]. Accordingly, we propose that differently oriented LNO films may be utilized as seed layers to control the growth of SRO films.…”
Section: Introductionmentioning
confidence: 84%